Seed size of common bean affects the utilization of stored reserves during germination - Siega, Yasmin Pincegher; Padilha, Matheus Santin; Coelho, Cileide Maria Medeiros; Ehrhardt-Brocardo, Natalia Carolina Moraes (Revista de Ciências Agroveterinárias, 2023)
The objective of the present study was to evaluate the physiological quality of bean seeds with different sizes, identifying the relationship of seed size with the mobilization and utilization of reserves in bean seeds. Seeds of the commercial cultivar IPR-88 Uirapuru and Iapar 81 were standardized and subsequently, three fractions were determined from individual weighing, being: small medium and large seeds. The physiological quality of the three fractions was determined by germination test, accelerated aging vigor test, and seedling performance (length) test. Reserve mobilization and utilization was measured at five days of seed hydration, where dry mass, reserve mobilization rate, reserve reduction rate, and reserve use efficiency were evaluated. The results showed that there was no difference between the fractions in the percentage of germination and accelerated aging. Considering the parameters that evaluated the mobilization and use of reserves, it was found that larger seeds form seedlings with greater dry mass, however, have lower rate of reserve mobilization and lower efficiency of use of their reserves. Thus, it is evident that the size of the seed influences the mobilization and use of reserves, so that seeds of the medium and small fraction present higher reserve use efficiency at five days of germination.